Factors in the Selection of Uterine Contraceptives in Women of Childbearing Age - Hasibuan, Ennysah; Harahap, Meilani; Pulungan, Nikmatul Khoiriyah (International Journal of Public Health Excellence (IJPHE), 2022)
Intrauterine contraceptives are devices or objects that are inserted into the uterus which are very effective, reversible and long-term, and can be used by all women of reproductive age. The study design was an observational analytic survey with a case-control design that was conducted by comparing those who did not use an intrauterine device (IUD) as a case with those who used an intrauterine device (IUD) as a control. The sampling method in this study is proportional. The population in this study were women with pus with a total sample of 96 people. The results of the bivariate analysis of knowledge p = 0.000 value obtained OR 9.348 (95% CI: 3.157-27.678), attitude p = 0.567 OR 0.567 (95% CI: 0.240-1.340), husband's support p = 0.031 value OR 2.929 (95% CI : 1,076-7,971) Service KB p = value 0.000 OR 5,909 (95% CI: 2,290-15,248). The most influential multivariate results from knowledge p = value 0.001 OR 6.472. The conclusion of the research is the relationship between knowledge, attitudes, husband's support and family planning services. And the most influential factor in choosing an IUD is the husband's attitude and support.